1949
DOI: 10.1002/bjs.18003614305
|View full text |Cite
|
Sign up to set email alerts
|

Some observations on the functional anatomy of inguinal hernia and its bearing on the operative treatment

Abstract: ANATOMY is at the present time in a phase of activity and expansion, and surgery is both an agent and a beneficiary of this activity. A principal feature is the change from a static to a functional concept of anatomy. The change of approach in the case of inguinal hernia has, however, been slow. The operation devised by Bassini (1890) was such an FIG. 379.-The right femoral and inguinal regions viewed from the inner aspect. (After a drawing of Hamilton Russell's to illustrate his article on femoral hernia, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1950
1950
1961
1961

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Ogilvie (1929) accepted the view of a muscular sphincter and considered it became incompetent from deficient muscular tone and increased intra‐abdominal pressure. Patey (1949) stimulated the exposed conjoined muscles electrically and concluded that the shutter‐like mechanism, as postulated by Keith, did not exist. He suggested that the main protective agent is a tautening of the transversalis fascia through the pull on its attachment to the deep surface of the transversalis muscle.…”
Section: Defence Mechanisms Of the Inguinal Canalmentioning
confidence: 99%
“…Ogilvie (1929) accepted the view of a muscular sphincter and considered it became incompetent from deficient muscular tone and increased intra‐abdominal pressure. Patey (1949) stimulated the exposed conjoined muscles electrically and concluded that the shutter‐like mechanism, as postulated by Keith, did not exist. He suggested that the main protective agent is a tautening of the transversalis fascia through the pull on its attachment to the deep surface of the transversalis muscle.…”
Section: Defence Mechanisms Of the Inguinal Canalmentioning
confidence: 99%
“…It may be absent or only slightly developed, or replaced by a lateral extension of the tendon or origin of the rectus muscle; but sometimes, when it is well developed, the conjoint tendon itself is continued farther laterally as a thin expansion which reaches the medial side of the deep abdominal ring so that then no interval is present between the lower border of transversus and the inguinal ligament (Walmsley, 1939). Patey (1949) as a result of electrical stimulation of the internal oblique and transversus muscles in hernia cases makes a definite statement in his summary of the functional anatomy of inguinal hernia that the shutter-like mechanism of the conjoint tendon does not exist. Rains (1951), however, p3ints out that the shutter action of conjoint tendon can only be demonstrated when the transversus and internal oblique muscles are attached to the iliopectineal line.…”
mentioning
confidence: 99%